Distribution of Adrenergic Receptor Subtypes and Responses to Topical 0.5% Apraclonidine in Patients With Blepharoptosis. Issue 6 (November 2018) - Park, Seong Jun; Jang, Sun Young; Baek, Ji Sun; Chin, Susie; Jang, Jae Woo
Abstract : Purpose: To determine the relationship between the distribution of adrenergic receptors in the human eyelid and the eyelid elevation after topically instilling 0.5% apraclonidine in blepharoptosis patients. Methods: A total of 26 blepharoptotic patients (30 eyelids) were included in the experimental study. Marginal reflex distance 1 was measured before and after topical instillation of 0.5% apraclonidine. Eyelids were divided into 2 groups according to the responses to topical 0.5% apraclonidine. Patients who positively responded to apraclonidine were classified as group A and those that negatively responded to it were classified as group B. Müller's muscle was obtained during the blepharoptotic surgery, followed by immunohistochemical staining and scoring. This study was approved by the Institutional Review Board of Kim's Eye Hospital and the study protocol adhered to the tenets of the Declaration of Helsinki. Results: α-1D staining intensity was significantly higher in group A than in B ( p < 0.001) and α-2C and β-1 staining intensities were significantly higher in group B than in A ( p < 0.001 and p < 0.05, respectively). The difference in β-2 staining intensity between groups A and B was not statistically significant. Conclusions: α-1D adrenoceptor was predominant in patients showing a positive response to topical 0.5% apraclonidine. Because apraclonidine has an α-1 agonistic effect, α-1D adrenoceptor may contribute to apraclonidine's elevating effect in patients with blepharoptosis. Abstract : The study revealed that α-1D adrenoceptor was predominant in patients with positive response to topical 0.5% apraclonidine, showing the possibility that α-1D adrenoceptor may contribute to apraclonidine's elevating effect in blepharoptotic patients.